Beyond conventional service economics: Utility services, service-product chains, and job services - Günther Schmid (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2000)
This essay intends to explore three innovative ways to foster job creation in services: First, the switch from product markets to utility markets would induce more and new types of user services. Such a switch would not only be more employment friendly but also foster a sustainable economic development compatible with ecological principles. The reorientation from products to utilities provides strong arguments for an emphasis on the framework conditions of services, for instance for lowering VAT in favour of labour intensive services, for forward regulation through (usually service enhancing) high quality standards, for deregulating market entry barriers, and for subsidising networks instead of individual products or services. Second, the thesis of cost disease has to be reconsidered in view of productivity enhancing possibilities by new technologies, and in view of innovative possibilities in managing specific income risks related to modern services. Service-product chains are the main ingredient for increasing productivity in services which is demonstrated in the field of art. Various approaches of social insurance in this field offer also inspiring ideas for risk management beyond the traditional welfare state. The most important policy conclusion related to this experience is the inclusion of consumers into the financing of social insurance. Third, the switch from transfers to persons with low earnings capacities to the support of peoples self-reliance through their own work could also induce increasing demand for already existing or new types of job services, and contribute especially to gender equality in the labour market. The central policy conclusion is the recommendation to turn social benefit entitlements (transfers) into vouchers for buying or co-financing job services. – – Dieser Essay skizziert drei innovative Wege zur Förderung der Beschäftigung in Dienstleistungen: Erstens würde die Abkehr von Produktmärkten zugunsten von Nutzungsmärkten mehr und neue Typen von Nutzungsdienstleistungen hervorrufen. Auf Nutzungsmärkten wird der unmittelbare Nutzen und nicht ein möglicherweise Nutzen leistendes Produkt gekauft. Solch eine Umorientierung würde nicht nur der Beschäftigung, sondern auch der Umwelt gut tun. Darüber hinaus lenkt diese Strategie die Aufmerksamkeit auf günstigere Rahmenbedingungen für Dienstleistungen, z. B. auf eine Herabsetzung der Mehrwertsteuern für arbeitsintensive Dienstleistungen, auf eine an Zukunftsmärkten orientierte Regulierung durch Qualitätsstandards, auf die Deregulierung von Markteintrittsbarrieren und auf die Subventionierung von Netzwerken anstelle von einzelnen Produkten oder Dienstleistungen. Zweitens muß die These der 'Kostenkrankheit' revidiert werden, da durch die neuen Technologien die Möglichkeiten gestiegen sind, die Produktivität auch von Dienstleistungen zu steigern und die mit vielen Dienstleistungen verbundenen Einkommensrisiken durch modernes Risikomanagement abzusichern. Dienstleistungs- Produkt-Ketten sind die wichtigste Form der Produktivitätssteigerung in Dienstleistungen, was am Beispiel des Künstlerarbeitsmarkts demonstriert wird. Die Entwicklung der Sozialversicherung in diesem Bereich bietet anregende Ideen für ein Risikomanagement, das über den traditionellen Wohlfahrtsstaat hinausgeht. Die wichtigste Folgerung für die Politik ist die Einbeziehung der Konsumenten in die Finanzierung der sozialen Sicherung. Drittens könnte die Umlenkung von Transferzahlungen an Bezieher mit geringem Einkommensvermögen in direkte Beschäftigungsunterstützung deren Selbstvertrauen stärken, mehr Nachfrage nach Beschäftigungsdienstleistungen hervorrufen und dadurch vor allem die Gleichstellung zwischen den Geschlechtern auf dem Arbeitsmarkt fördern. Es wird daher empfohlen, den Tausch von Ansprüchen auf Sozialleistungen oder Transferzahlungen in Gutscheine zum Kauf von Beschäftigungsdienstleistungen zu ermöglichen.
Keywords: 330; Dienstleistungssektor; Beschäftigungseffekt; Unternehmensdienstleistung; Produktivität; Sozialreform; Künstlerische Berufe; Deutschland